Construction and Activity of an All‐Organic Heterojunction Photocatalyst Based on Melem and Pyromellitic Dianhydride. Issue 12 (2nd June 2022) - Li, Yuxin; Jiang, Zeyu; Dong, Guohui; Ho, Wingkei
Abstract: Invited for this month′s cover is the group of Wingkei Ho at The Education University of Hong Kong. The Cover shows the effect of the number of heterojunction knots in an all‐organic photocatalyst on the separation of photogenerated carriers. The heterojunction knots could improve the migration eﬃciency of carriers between Melem and the formed pyromellitic diimide. The oxygen adsorbed on the surface of the material can be reduced by electrons to the reactive oxygen species superoxide anion (⋅O2 − ), thereby achieving the purpose of removing pollutants. The Research Article itself is available at 10.1002/cssc.202200477 . Abstract : "Construction of all‐organic heterojunctions can generate more photogenerated carriers…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202200477 . View the Front Cover here: 10.1002/cssc.202200876 .